Gestalt coaching : distinctive features - Bluckert, Peter (London : Routledge, 2020)
Gestalt Coaching: Distinctive Features makes Gestalt principles, values, and philosophy accessible to coaches of all backgrounds and explains how to apply them in practice. Peter Bluckert introduces 30 distinctive features of this approach, divided equally between theory and practice. The book provides concise but clear summaries of core concepts such as awareness and contact, the nature and power of unfinished situations, the Field perspective, the phenomenological approach, The Gestalt Cycle of Experience, and the nature of strategic and intimate interactions. Bluckert provides a set of practice guidelines and watch-outs for the Gestalt coach, information on training and development and several case examples to bring the approach to life. Gestalt Coaching reveals how this approach can be used in individual development, such as executive coaching, with groups and teams, and in wider social and political contexts. With a focus on personal growth and development and enhancing co-operation, dialogue, and relationships, this book will be an invaluable tool for coaches of all backgrounds in practice and in training, academics and students of coaching, and anyone interested in learning more about how to apply Gestalt principles in their personal and professional life.
List of Tables and Figures Introduction Part 1. THEORY -- Gestalt principles and key concepts 1. The emergence of a Gestalt coaching approach 2. The hallmarks of the Gestalt approach -- Part 1 3. The hallmarks of the Gestalt approach -- Part 2 4. Healthy self-regulation and creative adjustment 5. Figure and Ground 6. Staying with the 'What is' -- the phenomenological approach in action 7. The Field perspective -- the person in context 8. Context: balancing the strategic and intimate 9. The nature and power of unfinished situations 10. Awareness 11. Contact, and interruptions to contact 12. Ways we interrupt contact, and consequences -- Part 1 13. Ways we interrupt contact, and consequences -- Part 2 14. The Gestalt Cycle of Experience as an orienting framework SECTION 2. PRACTICE 15. Creating the conditions for deeper personal development and connection 16. The relational stance and dialogic attitude 17. Core principles in practice 18. Practitioner presence -- the intentional use of self 19. Experimentation and improvisation in Gestalt coaching 20. Individual-focused Gestalt experiments 21. Experiments in group and team contexts 22. The unit of work as a team learning experiment 23. Structured approaches to awareness raising 24. Support, challenge and dealing with complexity 25. Gestalt-based vertical leadership development programmes 26. Resourcing the client: relational know-how for dialogue and deeper connection 27. Practice guidelines for the Gestalt coach -- Part 1 28. Practice guidelines for the Gestalt coach -- Part 2 29. Watch-outs for Gestalt coaches 30. The training and development of Gestalt coaches Notes Referencing
OCLC-licensed vendor bibliographic record.
Keywords: Executive coaching; Gestalt psychology; PSYCHOLOGY / Mental Health